The Effect Of Sports Events On The Motivation And Interest Of Repeat Visit Tourists In The Lake Sipin Tourism Area, Jambi City - Ugi Nugraha; Ely Yuliawan; Ceppy Pradana (Universitas PGRI Palembang, 2022)
This study aimed to analyze the effect of organizing sporting events on revisit intention mediated by the tourist motivation in the tourism area of Danau Sipin, Jambi City. The population in this study were tourists who visited the tourist area of Danau Sipin, Jambi City. The sample in this study was selected by accidental sampling method. This method was chosen because it was difficult to determine the visitor data for tourist attractions because it changes every day, so the samples were the visitor that the researcher met randomly in the tourist area of Danau Sipin, Jambi City. Data analysis in this study used the Partial Least Square (PLS) approach with the help of the WarpPLS 7.0 software. The results of this study indicated that organizing sporting events had a direct effect on motivation and revisit intention. The results of this study also indicated that the sporting events had an indirect effect on revisit intention which was mediated by tourist motivation